2022
DOI: 10.1021/acs.est.2c07376
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Corona Dictates Mobility of Nanoplastics in Saturated Porous Media: The Critical Role of Preferential Binding of Macromolecules

Abstract: Nanoplastics are an increasing environmental concern. In aquatic environments, nanoplastics will acquire an eco-corona by interacting with macromolecules (e.g., humic substances and extracellular polymeric substances (EPS)). Here, we show that the properties of the eco-corona and, consequently, its ability to enhance the transport of nanoplastics vary significantly with the surface functionality of nanoplastics and sources of macromolecules. The eco-corona derived from the EPS of Gram-negative Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…HA is a typical component in real environment, and can affect the detection and migration of nanoplastics. 34,35 The characteristic ions of PMMA and PS were not influenced by various HA concentrations (Figure S6). The extraction efficiencies of PMMA and PS with various HA concentrations are shown in Figure 3c.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…HA is a typical component in real environment, and can affect the detection and migration of nanoplastics. 34,35 The characteristic ions of PMMA and PS were not influenced by various HA concentrations (Figure S6). The extraction efficiencies of PMMA and PS with various HA concentrations are shown in Figure 3c.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After heteroaggregation of NPs with natural colloids, an encapsulation layer of NPs covered by natural colloids tends to form, which is an eco-colloid layer, also known as an eco-corona . Eco-corona usually shows colloidal stability, strong biosorption capacity and pollutant transport capacity, which leads to altered aggregation and dispersion of NPs and affects their stability in the aquatic environment. , Since electrolytes in the aquatic environment interact with natural colloids, the role of natural colloids on NPs is specifically analyzed according to the level of electrolyte content (i.e., ionic strength) in the aquatic environment . In the aquatic environment that do not contain large amounts of electrolytes, the presence of EPS and HA increases the stability of NPs in the aquatic environment by increasing the steric hindrance and electrostatic repulsion, making the NPs less likely to aggregate.…”
Section: Reaction With Natural Colloidsmentioning
confidence: 99%
“…Results suggested that the pH and chemical heterogeneity of BFRs is essential in determining the ternary BFR-protein-PN interactions. The resultant protein orientation, corona thickness, and particle aggregation status may greatly influence PN transport, cellular uptake, cytotoxicity, 40 and environmental mobility, 41 which eventually govern their fate.…”
Section: Hfr-induced Aggregation Without Protein Structuralmentioning
confidence: 99%